Optimal design of water supply networks for enhancing seismic reliability. (February 2016) - Yoo, Do Guen; Kang, Doosun; Kim, Joong Hoon
Abstract: The goal of the present study is to construct a reliability evaluation model of a water supply system taking seismic hazards and present techniques to enhance hydraulic reliability of the design into consideration. To maximize seismic reliability with limited budgets, an optimal design model is developed using an optimization technique called harmony search (HS). The model is applied to actual water supply systems to determine pipe diameters that can maximize seismic reliability. The reliabilities between the optimal design and existing designs were compared and analyzed. The optimal design would both enhance reliability by approximately 8.9% and have a construction cost of approximately 1.3% less than current pipe construction cost. In addition, the reinforcement of the durability of individual pipes without considering the system produced ineffective results in terms of both cost and reliability. Therefore, to increase the supply ability of the entire system, optimized pipe diameter combinations should be derived. Systems in which normal status hydraulic stability and abnormal status available demand could be maximally secured if configured through the optimal design. Highlights: We construct a seismic reliability evaluation model of water supply system. We present technique to enhance hydraulic reliability in the aspect of design. Harmony search algorithm is applied in optimal designs process. The effects of the proposed optimal design are improved reliability about by 9%. Optimized pipe diameter combinations should be derived indispensably.